ANALYSIS OF THE INFLUENCE OF BUSSINESS RISK AND FINANCIAL RISK AGAINST THE PROFITABILITY OF TELECOMMUNICATIONS SUB SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (2012-2019 PERIOD) - Sondang; Ganda T. Hutapea (Fundamental Management Journal, 2022)
This research aimed to analyze the influence of business risk and financial risk both partially and simultaneously against Return on Equity of telecommunications companies listed on the Indonesia Stock Exchange during 2012-2019 period. The samples in this study were 4 telecommunications companies, which publishes the annual report during 2012-2019 period. Analysis teqnique used is multiple linear regression. The result of these findings of t test shown that business risk partially has no effect against Return on Equity, based on the findings shown that a significant value of 0.561>0.05 and financial risk has effect against Return on Equity, based on the findings shows that a significant value of 0.023<0.05. The findings state that business risk and financial risk simultaneously have no effect against Return on Equity, this is shown that a significance value (0.062>0.05). The result of data shown that the coefficients of determination is 0,174 or 17,4%. Keywords: Business Risk, Financial Risk, Profitability